2005
DOI: 10.1111/j.0022-1112.2005.00658.x
|View full text |Cite
|
Sign up to set email alerts
|

Response to conspecific and heterospecific alarm cues by pumpkinseeds in simple and complex habitats: field verification of an ontogenetic shift

Abstract: Three focal size classes [small (<40 mm, standard length, L S ), medium (40-80 mm L S ) and large (>80 mm L S )] of pumpkinseed Lepomis gibbosus were exposed to conspecific or one of three heterospecific chemical alarm cues under one of three levels of habitat complexity (low, intermediate and high). Under low and intermediate habitat complexities, pumpkinseeds <80 mm L S exhibited a significant antipredator response when exposed to the chemical alarm cues of heterospecific prey guild members (largemouth bass … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
1

Year Published

2006
2006
2023
2023

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(13 citation statements)
references
References 43 publications
1
11
1
Order By: Relevance
“…These results indicate that in situations where visual signals are compromised, prey will increase their response to chemical information, as has been found in mate-selection scenarios [11]. The significant effects of turbidity on the antipredator behaviour of a marine fish, identified here, support previous studies on freshwater fish at similar turbidities [3], and when visual information was reduced via habitat complexity [15] rather than turbidity.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…These results indicate that in situations where visual signals are compromised, prey will increase their response to chemical information, as has been found in mate-selection scenarios [11]. The significant effects of turbidity on the antipredator behaviour of a marine fish, identified here, support previous studies on freshwater fish at similar turbidities [3], and when visual information was reduced via habitat complexity [15] rather than turbidity.…”
Section: Discussionsupporting
confidence: 85%
“…increased antipredator behaviours [15]. As per the 'sensory compensation' hypothesis, A. polyacanthus increased its reliance on chemical input to assess its risk of predation in situations where visual information was limited.…”
Section: Discussionmentioning
confidence: 97%
“…This hypothesis assumes that reduced anti-predator behaviour and visual risk perception should result in higher or similar ingestion of invertebrates in turbid compared to clear waters. Conversely, our results indicated that fish shoals exhibited stronger predator avoidance behaviour in turbid than in clear water (Golub, Vermette & Brown, 2005;Swanbrow Becker & Gabor, 2012). We suggest that turbidity-induced visual obstruction amplifies the negative effects of predator presence on intermediate consumer fish feeding behaviour, ultimately resulting in higher prey survival.…”
Section: Discussionmentioning
confidence: 56%
“…Many groups of freshwater fishes produce chemical cues in the epidermis which are released into the water following mechanical damage, as would occur during a predation event [8]. Upon detection by conspecific receivers, these cues have been shown to elicit a suite of antipredator or alarm responses [9] in centrarchid [10], salmonid [11], cyprinid [12], cyprinodontiform [2], esocid [13], and poeciliid [14] species. Due to their manner of release, these chemical cues cannot be manipulated by a predator and likely serve as reliable indicators of increased risk to receivers subject to similar predation pressures [15], which is not always the case with potentially misleading visual cues [3].…”
Section: Introductionmentioning
confidence: 99%